2013
DOI: 10.11138/mltj/2013.3.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Subcoracoid impingement and subscapularis tendon: is there any truth?

Abstract: SummarySubcoracoid impingement and stenosis have been described related to anterior shoulder pain and subscapularis tendon tears, but the pathogenesis and related treatment of this condition has still not been explained properly. Variability of coracoid morphology has been described and both traumatic and iatrogenic factors can modify it. Some authors referred this to a primary narrow coracohumeral distance with different threshold values defined as increased risk factor for subscapularis and antero-superior R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
0
26
0
2
Order By: Relevance
“…Some studies have reported that a short coracohumeral distance contributes to subscapularis tendon pathologies (1417). In our study, the coracohumeral distance was significantly narrower in patients who had a cyst within the lesser tuberosity, which likely resulted in subscapularis tendon pathologies being more frequent in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that a short coracohumeral distance contributes to subscapularis tendon pathologies (1417). In our study, the coracohumeral distance was significantly narrower in patients who had a cyst within the lesser tuberosity, which likely resulted in subscapularis tendon pathologies being more frequent in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Subcoracoid impingement has been implicated as a rare cause of anterior shoulder pain and abnormalities. 1 , 7 - 9 , 14 , 20 , 22 - 24 Gerber et al 8 provided the first comprehensive description of subcoracoid impingement. These authors described the clinical syndrome of subcoracoid impingement and helped to delineate the anatomy of this entity using computed tomography.…”
mentioning
confidence: 99%
“…Previous studies indicated that the impingement could be caused between the proximal humerus and the coracoid process, particularly in the shoulder motion of flexion with internal rotation. 3 , 10 In addition, passive maneuver of flexion with horizontal abduction has been clinically used as the provocative test for subcoracoid impingement, namely coracoid impingement test 5 or modified Kennedy-Hawkins test. 21 The present study clearly demonstrated that 3DCHD significantly altered in association with shoulder flexion with horizontal adduction, which simulated the coracoid impingement test.…”
Section: Discussionmentioning
confidence: 99%
“…There might be some differences in CHD between the supine position and the upright position with the shoulder loaded by gravity or the weight of the arm. 3 , 17 Second, we analyzed the movement patterns estimated under sequential static conditions: it may not completely reflect the shortest CHD during dynamic motion. From this perspective, 2D-3D registration technique using fluoroscopy might be more precisely evaluated than our method using MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation